QUALITY CHARACTERISTIC OF CARRAGEENAN SEAWEED KAPPAPHYCUS ALVAREZII WITH DIFFERENT BLEACHING TREATMENT: QUALITY ASSESSMENT OF ORGANOLEPTIC AND PROXIMATE - Irma Suryani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
This research was aimed to determine the effect of bleaching method at different bleaching places and type ofwater soaking toward the quality of seaweed. This research uses a randomized factorial design. It consists of 2factors;which are type of bleaching place and type of soaking. At the first factor, there are two levels, namely thelevel of seawater and freshwater. On the second factor there are two levels, namely the level of land soaking andsea soaking. The results of the research showed that the bleaching treatment at sea with the type of sea watersoakingwas thebest treatment based onseveral parameters: byProximate,Organoleptic, and bleaching treatmentswith different soaking.Keywords: Kappaphycus alvarezii, carrageenan, organoleptic, proximate.